DOES TWO PARALLEL LATERAL-ONLY PIN CONFIGURATION PROVIDE STABLE OSTEOSYNTHESIS FOR PEDIATRIC SUPRACONDYLAR HUMERUS FRACTURES? - Bulbul, Murat; Ayanoglu, Semih; Imren, Yunus; Kahraman, Sinan; Esenyel, Cem Zeki; Gurbuz, Hakan (My University, 2011)
Objective: To evaluate clinical and radiographic outcome of closed reduction and percutaneous pinning of pediatric supracondylar humerus fractures using lateral two parallel pinning versus lateral two parallel with one medial pinning technique.